A Smart Dental Floss for Biosensing of Glucose. Issue 5 (12th February 2019) - Sha, Pengju; Luo, Xiaojin; Shi, Weihua; Liu, Yiqun; Cui, Yue
Abstract: The development of a simple directly wearable approach for the rapid, specific and sensitive determination of biomarkers is of great importance to a variety of biomedical applications. Dental floss can provide a unique device platform for sensing of oral biomarkers. We show here for the first time the development of a smart dental floss for biosensing of glucose. The sensor was made by painting carbon graphite ink and Ag/AgCl ink on dental floss. Via the immobilization of glucose oxidase, we show the detection of glucose with a detection range of 0.048 mM to 19.5 mM and a response time of about 2 min. It is expected that our results could provide new exciting opportunities for the development of various flexible smart sensing devices in oral health applications. Abstract :